DYNAMIC PLANNING INDICATORS FOR OPTIMISING THE ENERGY MODERNISATION OF RESIDENTIAL HOUSING STOCK - S. K. Bayramukov; Z. N. Dolaeva; M. B. Kappusheva (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. In the article, the problem of the optimisation of the energy modernisation of residential housing is examined. Methods. A mathematical model for the optimisation of energy use is developed with the use of dynamic programming techniques. Results. The proposed method of assessing the effectiveness of comprehensive energy-saving measures can improve the quality of decision-making on housing recovery and increase its energy modernisation. The application of mathematical modeling allows for the distribution of funds to projects so that the implementation of organisational and technological solutions consistently implement measures that will lead to optimal social and economic effects. The developed mathematical model also allows the amount of quality housing to be maximised through the implementation of energy-saving and other measures when upgrading the housing stock. Problems concerning the renovation of housing stock are analysed. The concept of housing energy modernisation is introduced. The principal energysaving technologies in housing modernisation are distinguished. A schema for the optimal allocation of funds for energy-saving measures is described. It is assumed that the optimal solution is obtained independently of the number of steps and the initial supply of invested capital.Conclusion. The energy modernisation of the housing stock leads to a reduction in the expenditures of citizens on housing and utilities services, contributing to an increase in the integral index of comfort. A generalised method for optimal control of the housing stock is implemented on the basis of the provided schema for dynamic scheduling of the optimal distribution of funds for energy-saving measures.